Uji Antibakteri Fraksi Aktif Ekstrak Aseton Kulit Batang Shorea acuminatissima terhadap Staphylococcus aureus dan Pseudomonas aeruginosa Multiresisten antibiotik - Prayitno, Imam; Saroyobudiyono, Haryoto; Indrayudha, Peni (Jurnal Farmasi (Journal of Pharmacy), 2013)
Infection disease has a serious problem in Indonesia, including antibiotic resistance of microorganisms. One of the tropical forest plant in Indonesia is Shorea accuminatissima which included in Dipterocarpaceae and reported to have compound content of phenolic with biological activity like antibacterial, antioxidant and antifungi. This research aim to know the antibacterial activities of acetone extract and active fraction of acetone extract to S. aureus and P. aeruginosa multiple resistance antibiotic.Acetone extract obtained with maceration method, then tested the antibacterial activity. Later, acetone extract fractioned use Vacuum Liquid Chromatography (VLC). Each fraction tested by bioautographic to determine the antibacterial activities using a filter paper disc method with S. aureus and P. aeruginosa. Fraction with the biggest radical zone is an active fraction, then tested the antibacterial activity. The lowest concentration that kills bacterial growth conceived as Minimum Bactericidal Concentration (MBC).Research show that acetone extract of Shorea accuminatissima stembark have the MBC values at 0,25% to S. aureus multiple resistance antibiotic and 1% to P. aeruginosa multiple resistance antibiotic. Active fraction is fraction C. Active fraction have the MBC values at 0,125% to S. aureus multiple resistance antibiotic and 0,25% to P. aeruginosa multiple resistance antibiotic.